2015
DOI: 10.1002/jsfa.7256
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profile of the tomato dwarf cultivar Micro‐Tom and comparative response to saline and nutritional stresses with regard to a commercial cultivar

Abstract: The mutations leading to the dwarf phenotype did not greatly alter the metabolite profiles but studies using Micro-Tom as a plant model should consider the lower capacity for sugars and organic acids under saline conditions and the greater tolerance to nutrient limitation of the dwarf variety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 42 publications
6
25
0
Order By: Relevance
“…From the data of total and marketable yield and leaf biomass obtained in this study, it can be concluded that, for tomato plants of the variety ‘Optima’ cultivated with non-saline NS, the DFT system is more productive. The values obtained are very similar to those found in other work with the same variety and soilless culture system 14 . The higher fruits yield derived from a greater mean fresh weight per fruit, while the number of fruits was not affected by the soilless culture system.…”
Section: Discussionsupporting
confidence: 90%
“…From the data of total and marketable yield and leaf biomass obtained in this study, it can be concluded that, for tomato plants of the variety ‘Optima’ cultivated with non-saline NS, the DFT system is more productive. The values obtained are very similar to those found in other work with the same variety and soilless culture system 14 . The higher fruits yield derived from a greater mean fresh weight per fruit, while the number of fruits was not affected by the soilless culture system.…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown that moderate stress conditions may improve fruit quality through higher concentration of flavor compounds (Zheng et al, 2013; Albert et al, 2016a; Albert et al, 2016b). In several studies, the concentrations of sugars, organic acids, vitamin C, phenolic compounds and carotenoids increased in tomato fruits in response to water deficit, salinity, or heat (Saito et al, 2009; Patanè et al, 2011; Zushi and Matsuzoe, 2015; Albert et al, 2016b; Flores et al, 2016; Marsic et al, 2018). However, increased CO 2 levels increased fruit production but decreased fruit quality (Mamatha et al, 2014).…”
Section: Effects Of Abiotic Stress On Tomato Fruit Metabolismmentioning
confidence: 99%
“…However, increased CO 2 levels increased fruit production but decreased fruit quality (Mamatha et al, 2014). Nevertheless, metabolic modifications in tomato fruits in response to abiotic stress may be cultivar-dependent (Sánchez-Rodríguez et al, 2012a; Sánchez‐Rodríguez et al, 2012b; Zushi and Matsuzoe, 2015; Albert et al, 2016b; Albert et al, 2016a; Flores et al, 2016; Marsic et al, 2018). Table 1 summarizes some recent studies regarding the impact of abiotic stress occurring during plant growth on primary and secondary metabolism of tomato fruits.…”
Section: Effects Of Abiotic Stress On Tomato Fruit Metabolismmentioning
confidence: 99%
“…Adequate K nutrition greatly influences the synthesis of sucrose and starch in plants such as apple (Mosa et al, 2015), muskmelon (Lester et al, 2010), tomato (Almeselmani et al, 2010) and strawberry (Ahmad et al, 2014). However, K levels have different effects on organic acid metabolism depending on the plant species (Etienne et al, 2014; Flores et al, 2015; Niu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%